Harmonization of Investment and Local Wisdom: an Ideal Model of Investment Regulation Based on Local Wisdom in Bali's Tourism Sector - Ida Ayu Putu Sri Astiti Padmawati; Ida Ayu Ratna Kumala; Riri Irmanti; Dewa Gede Edi Praditha; Gede Agung Wirawan Nusantara (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
The influx of investment then has a significant impact on the social life of Balinese indigenous people in preserving their local wisdom. This article raises the issue of the rapid phenomenon of investment in Bali which has the impact of dualism of interests on indigenous peoples who must maintain their local wisdom and on the one hand must also follow the development of economic flows to support their lives. This paper is normative legal research using the method of statutory approach, conceptual approach, and sociological approach. This research argues that the harmonization of tourism investment with the value of Tri Hita Karana in Bali creates a balance between economic benefits and preservation of local cultural identity. The ideal investment model in Bali requires the collaboration of investors, government, and indigenous people through adaptive regulations based on local wisdom